COVID-19 pandemic’s effects on the quality of pregnant women’s emergency treatment: review of two cases from a medical center in northern Taiwan (2020)
The spread of COVID-19 has resulted in a high risk of infection in hospitals worldwide. The medical staff in emergency rooms, in particular, have borne the brunt of the pandemic, and strict protection measures are needed to avoid infection in these units. Taiwan as a whole has performed extremely well in this epidemic, an achievement that has been acknowledged internationally. This success can be attributed to the Taiwan Epidemic Prevention Management Center’s extensive experience and courageous strategy. The emergency department professionals of all hospitals, in conjunction with the outstanding performance of the center’s policy, have also done much to control the infection’s spread. However, excessive protection can also negatively affect patients’ safety and the quality of medical care, especially for pregnant and parturient women. This article uses two actual cases from a medical center in northern Taiwan to discuss the impact of COVID-19 on pregnant women. This case study serves to highlight that, to ensure more effective coordination during severe epidemics, a comprehensive infection prevention plan should be formulated. In addition, pregnant women’s human rights must be safeguarded so that various protective mechanisms can be effectively used to achieve win-win solutions. Hospitals need to plan their production methods and timing in advance for when pregnant patients are in critical condition. The findings include that obstetricians recommend caesarean sections as a safer method in during epidemics. Emergency room physicians and obstetricians should also actively assist mothers prepare for birth to enhance maternal and fetal safety.